Metabolic Profiling of Exercise-induced Autophagy-dependent Metabolites in Mouse Plasma - Fadel, Joanna (2024)
Exercise has been shown to exert beneficial effects on cognitive function and mental health, with autophagy playing a crucial role in mediating these effects. However, the underlying mechanism between exercise-induced metabolic changes and autophagy remains largely unexplored. This study will tackle the identification of exercise-induced autophagy-dependent metabolic changes in mouse plasma using metabolomic analysis. Male C57BL/6J mice were divided into sedentary and exercise groups receiving either saline or chloroquine (CQ) to inhibit the autophagic pathway. Liquid chromatography-mass spectrometry (LC-MS) was used to analyze the plasma samples. Multivariate statistical analyses, including principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), and orthogonal PLS-DA (OPLS-DA), were performed to identify differentially expressed metabolites and potential biomarkers. Our results show that exercise induced distinct metabolic changes in mouse plasma, with several metabolites, including pregeijerene, androsterone glucuronide, meproscillarin, and N-acetyl methionine, showing significant increases in the exercise group. These changes were largely attenuated by CQ treatment, suggesting their dependence on autophagy. Pathway analysis revealed that steroid hormone biosynthesis was a critical pathway affected by exercise and autophagy inhibition. Other significant pathways included arginine and proline metabolism, biosynthesis of unsaturated fatty acids, linoleic acid metabolism, and tryptophan metabolism. This study demonstrates the significant changes in the plasma metabolome induced by exercise, which are partially mediated by autophagy. The identification of specific metabolites and pathways affected by both exercise and autophagy inhibition provides new insights into the molecular mechanisms underlying the beneficial effects of exercise on health and cognitive function. These findings may contribute to the development of an exercise pill that would mimic the beneficial effects of physical exercise for patients with neurodegenerative or psychiatric diseases.